Psychometric properties of the Persian version of the Suicidal Ideation Attributes Scale among Iranian college students - Nazari, Fatemeh; Kianimoghadam, Amir Sam; Jamshidmofid, Pardis; Norouzi, Mohammad Reza (Frontiers in Psychiatry, 2025)
BackgroundSuicidality is a major global health problem and the second leading reason of mortality in 15–29-year-olds, and a growing subgroup of these youths are students. The present study aimed to evaluate the psychometric properties of the Persian version of the Suicidal Ideation Attributes Scale (SIDAS) among Iranian college students.MethodA total of 398 Iranian college students completed study measures online. The Beck Scale for Suicide Ideation, Beck Hopelessness Scale, and Connor–Davidson Resilience Scale were chosen for evaluating concurrent and divergent validities. The content validity index (CVI) index was calculated in order to check the face validity and content validity. Confirmatory factor analysis was performed to confirm the factors of the SIDAS. Finally, receiver operating characteristic (ROC) curves were constructed to assess scale sensitivity and specificity.ResultsAccording to the findings, 286 (71.9%) of the participants were women. The average age of the sample was 23.9 years. According to this study, the Persian version of the SIDAS (SIDAS-P) demonstrated high internal consistency (a = 0.799), a unifactorial structure, a moderate correlation with the Beck Scale for Suicide Ideation (BSSI), and a negative moderate divergent validity with the Connor–Davidson Resilience Scale. Furthermore, the ROC curve analysis [area under the curve (AUC) = 0.909] indicated that the SIDAS-P could distinguish individuals with a high risk for suicidal behaviors (scores higher than 6.5 on the SIDAS are above the low risk for suicide).ConclusionThe findings support that the SIDAS is a valid and reliable online instrument for screening suicidal ideations in a population of non-clinical college students in Iran. To establish its clinical utility, further research should test its psychometric properties in clinical populations with different mental health problems.